2013
DOI: 10.1063/1.4820255
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanisms of GaSb heteroepitaxial films on Si with an AlSb buffer layer

Abstract: The initial growth stages of GaSb epilayers on Si substrates and the role of the AlSb buffer layer were studied by high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). Heteroepitaxy of GaSb and AlSb on Si both occur by Volmer-Weber (i.e., island mode) growth. However, the AlSb and GaSb islands have distinctly different characteristics as revealed through an atomic-resolution structural study using Z-contrast of HAADF-STEM imaging. While GaSb islands are sparse and three dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 35 publications
3
34
0
3
Order By: Relevance
“…Thin AlSb buffer layers have been shown to promote the growth of improved-quality GaSb epilayers, through a mechanism of action thought to result from the creation of small islands of AlSb acting as sites where 2D growth is energetically favoured. [8][9][10][11] In addition, various groups have already demonstrated III-V lasers on Si substrates. [12][13][14][15] Ultimately, growth of Sbbased materials on Si offers the possibility to integrate mid-infrared sources and detectors with CMOS circuitry.…”
mentioning
confidence: 99%
“…Thin AlSb buffer layers have been shown to promote the growth of improved-quality GaSb epilayers, through a mechanism of action thought to result from the creation of small islands of AlSb acting as sites where 2D growth is energetically favoured. [8][9][10][11] In addition, various groups have already demonstrated III-V lasers on Si substrates. [12][13][14][15] Ultimately, growth of Sbbased materials on Si offers the possibility to integrate mid-infrared sources and detectors with CMOS circuitry.…”
mentioning
confidence: 99%
“…With the large mismatch between GaSb and Si ($12.2%), the islands emerged with the strains released in the wetting layer [18]. Vajargah et al [14] have reported the high contact angle between the GaSb islands and the Si substrates. High contact angle means that Ga atoms and Sb atoms absorbed on GaSb islands consume less energy than on Si directly.…”
Section: Resultsmentioning
confidence: 97%
“…However, few studies have focused on GaSb grown on Si by metal-organic chemical vapor deposition (MOCVD). By large lattice mismatch in the GaSb/Si heterostructures ($12.2%), GaSb nucleated directly on Si and is considered to grow in Volmer-Weber (VW) mode from the nucleation stage [14][15][16]. And it is difficult to control the size and density of the nanostructures grown in VW mode.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this, in this work, we theoretically predict morphology of exposed surfaces and growth direction of biaxially tensile-strained GeNWs on a relaxed GaSb template that can be grown directly on Si with an AlSb buffer layer [16, 20]. We choose {110}, {105}, and {111} as exposed surfaces of lateral GeNWs and compare the total energy change in the steady-state system.…”
Section: Introductionmentioning
confidence: 93%